Isolation and Identification of Pathogenic Microorganisms from Houseflies (Global Journal of Science Frontier Research, 2018)
The housefly, Musca domestica, is a fly of the suborder Cyclorrhapha. It is an important vector for transmission of pathogenic microorganisms including bacteria, fungi and parasites. A total of 27 houseflies were collected, 9 each from dumpsite, canteen and indoor premise with the use of insect traps. The bacteria isolates obtained are: Escherichia coli, Salmonella species, Pseudomonas species, Shigella species, Klebsiella species, Staphylococcus species, Streptococcus species, Bacillus species and Proteus species. The fungi isolated are Aspergillus species, Penicillium species, Alternaria species and Fusarium species. The parasites obtained include Gairdia lamblia, Entamoeba histolytica, Enterobius vermicularis and Strongyloides species. Dumpsite had the highest percentage occurrence of microorganisms, followed by indoor and food canteen which had the lowest percentage occurrence. The presence of these pathogenic microorganisms in food canteens, indoor toilets and dumpsite implied a possible risk of transmission of the pathogens from the houseflies to humans thereby causing diseases; hence, the need to step up control measures against the insects.
Keywords: housefly; musca domestica; bacteria; fungi; parasites; food canteens; toilets and dumpsites